Using Syndromic Surveillance for All-Hazards Public Health Surveillance comprehensive review - Ali Hassan Alfayez et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Syndromic surveillance has become a vital tool in monitoring and responding to public health threats, including infectious disease outbreaks, environmental hazards, and bioterrorism. This approach uses real-time health-related data, such as emergency department visits and over-the-counter drug sales, to identify patterns indicative of emerging health risks. While syndromic surveillance has demonstrated significant successes in early detection and rapid response, it faces challenges, including data quality, interoperability, and maintaining privacy. This review examines the current applications, strengths, and limitations of syndromic surveillance and discusses opportunities for future advancements to address all-hazards public health surveillance needs. Received Date: July 08, 2024 Accepted Date: July 29, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/301 DOI: https://doi.org/10.5281/zenodo.14588219